Advokat Dalam Perspektif Hukum Islam dan Hukum Positif - Fitrah Humairah; Vivin Kadriani Matondang; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Advocates, according to Law no. 18 of 2003 concerning Advocates, is someone whose role is to provide legal assistance both inside and outside the court. Legal consultations, legal assistance, exercising power of attorney, representing, accompanying, defending, and carrying out other legal actions on behalf of clients are services that will be offered by advocates. Lawyers can also function as mediators in the pursuit of truth and the protection of justice, Participate in protecting human rights and offer free and independent legal defense. But in reality, the legal profession has advantages and disadvantages in society, especially in its role in providing legal services. As a result, a lawyer who represents clients in religious courts often does so to assist them or advise them legally to win public sympathy. Compliance with these guidelines can help reduce deviant behavior so that procedures can be considered. Keywords: Advocate, Islamic Law, Positif Law